The world that came in from the cold : perspectives from East and West on the Cold War - Gabriel Partos. (Royal Institute of International Affairs : BBC World Service, 1993)
"Based on the BBC World Service series, The world that came in from the cold." Includes bibliographical references (p. 292-293) and index.